FOREIGN RELATIONS OF THE BUKHARA PEOPLE’S SOVIET REPUBLIC WITH IRAN: DIPLOMATIC AND TRADE RELATIONS (1920–1924) (Web of Teachers: Inderscience Research, 2026)
This article analyzes the foreign relations of the Bukhara People’s Soviet Republic with Iran during 1920–1924, focusing on diplomatic and trade relations. The study examines the main directions of BPSR’s foreign policy and evaluates the political and economic significance of relations with Iran in regional and international contexts.